PENATALAKSANAAN FISIOTERAPI DENGAN PENERAPAN KOMBINASI ULTRASOUND (US) DAN NEUROMUSCULAR TAPING (NMT) DALAM MENURUNKAN SKALA NYERI PADA KONDISI TRIGGER FINGER - Yose Rizal (LPPM Universitas Abdurrab, 2023)
Trigger finger, also known as stenosing tenosynovitis, is a common hand disorder. A trigger finger is a limited or locked finger when bent and stretched. Disproportionate thickening and narrowing of the retinacular sheath relative to the flexor tendons occurs due to hypertrophy and metaplasia of fibrocartilage on the surface of the tendon pulleys. The main clinical finding is a temporary locking of the finger when bent, followed by a painful snap when extended. The purpose of this study was to determine the decrease in trigger finger pain after the administration of Ultrasound (US) and Neuromuscular Taping (NMT) interventions. This study uses the case study method. The sample for this study was a 42-year-old woman who was given physiotherapy intervention in the form of a combination of Ultrasound (US) and Neuromuscular Taping (NMT) six times for two weeks. Pain was measured by the Visual Analogue Scale (VAS). The results of the study show that giving Ultrasound (US) and Neuromuscular Taping (NMT) can reduce pain in trigger finger sufferers. Keywords: Trigger Finger, Ultrasound, Neuromuscular Tapping (NMT), Pain